THE EFFECTIVENESS OF PADLET LEARNING MEDIA ON IMPROVING STUDENTS' COGNITIVE HISTORY LEARNING OUTCOMES ON THE MATERIAL OF THE STRUGGLE FOR EUROPEAN NATIONS' HEGEMONY IN THE ARCHIPELAGO GRADE XI OF SMAN 11 PEKANBARU: Efektivitas Media Pembelajaran Padlet Terhadap Peningkatan Hasil Belajar Kognitif Sejarah Siswa Pada Materi Perebutan Hegemoni Bangsa Eropa Di Nusantara Kelas XI SMAN 11 Pekanbaru - Dimas Agung Prasetio; Bunari; Rizki Ananda Hasibuan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to assess the effectiveness of Padlet learning media in improving students' cognitive learning outcomes in history, particularly in the topic of the struggle for European hegemony in the archipelago, in grade XI students at SMAN 11 Pekanbaru. This study employed a quantitative approach with a quasi-experimental design, employing a pre-test and post-test non-equivalent control group design. The sample consisted of two groups: experimental group XI 2, consisting of 34 students who received Padlet learning media, and control group XI 1, consisting of 35 students who did not receive the same treatment. Data were collected through test sheets and analyzed using validity, reliability, normality, homogeneity, t-tests, and effectiveness tests for Padlet learning media. The results showed that the implementation of Padlet-based learning media significantly improved the cognitive learning outcomes of grade XI students at SMAN 11 Pekanbaru. The experimental group using Padlet achieved an average post-test score of 81,69, higher than the 75,36 score obtained by the Padlet-based learning media. The t-test showed a significance of 0,001 < 0,05. The effectiveness of Padlet media is classified as moderate with an N-Gain score of 60.17%, indicating that Padlet successfully transforms students into active knowledge builders. Furthermore, Padlet also trains higher-order cognitive skills according to Bloom's Taxonomy, encouraging analysis, evaluation, and the creation of logical arguments. With its collaborative features and access to various digital sources, Padlet has proven to be an effective solution for interactive and student-centered history learning